Effectiveness of Systemic Approach-Based Program on Developing Linguistic Written Performance among Advanced-Level of Non-Native Arabic Language Learners - Mohamed alam eldeen (International Journal of Instructional Technology and Educational Studies)
The current study aims to identify the effectiveness of a program based on the systemic approach in developing written linguistic performance and the attitude towards language learning among advanced-level of non-native Arabic learners. For the end of this goal, the researcher chose a group of advanced-level of non-native Arabic learners as a sample of the study. Moreover, the researcher recognized the linguistic performance skills (reading and writing) suitable for the advanced level of non-native Arabic learners. Hence, the study comprises the following tools: (1) a linguistic performance test in reading is constructed, after ensuring its validity and reliability, to measure the level of reading skill among non-native Arabic learners; (2) a test of written linguistic performance has been designed, after ensuring its validity and reliability, to measure the level of writing skill among non-native Arabic students; (3) an analytical rating list was constructed to evaluate the writing test for advanced level of non-native Arabic students; (4) a scale for the attitude towards learning Arabic language was also constructed for advanced level of non-native Arabic learners, which subsequently presented to experts for adjustments it and ensure its validity and reliability; (5) finally, a program based on the systemic approach was also built to develop the linguistic (reading - writing) performance of advanced level of non-native Arabic learners. The researcher applied the study tools via pre- and post-measurements. Ultimately,